Opportunities and challenges for the clinical translation of structured DNA assemblies as gene therapeutic delivery and vaccine vectors. (15th July 2020) - Dobrovolskaia, Marina A.; Bathe, Mark
Abstract: Gene therapeutics including siRNAs, anti‐sense oligos, messenger RNAs, and CRISPR ribonucleoprotein complexes offer unmet potential to treat over 7, 000 known genetic diseases, as well as cancer, through targeted in vivo modulation of aberrant gene expression and immune cell activation. Compared with viral vectors, nonviral delivery vectors offer controlled immunogenicity and low manufacturing cost, yet suffer from limitations in toxicity, targeting, and transduction efficiency. Structured DNA assemblies fabricated using the principle of scaffolded DNA origami offer a new nonviral delivery vector with intrinsic, yet controllable immunostimulatory properties and virus‐like spatial presentation of ligands and immunogens for cell‐specific targeting, activation, and control over intracellular trafficking, in addition to low manufacturing cost. However, the relative utilities and limitations of these vectors must clearly be demonstrated in preclinical studies for their clinical potential to be realized. Here, we review the major capabilities, opportunities, and challenges we foresee in translating these next‐generation delivery and vaccine vectors to the clinic. This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Biology‐Inspired Nanomaterials > Nucleic Acid‐Based Structures Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Virus‐like nucleic acid nanoparticles can be programmed to deliver and release CRISPR RNPs, HDR templates, and siRNAs either alone, or in combination, for next‐generation in vivo gene therapeutic applications.